Quo Vadis Banking Union? Discussions over the Resolution of Banks - Zielińska, Klaudia Alicja (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Transferring the right to make the decision concerning a bank’s resolution onto the international level has long been the bone of contention between the European Union’s Member States. The aim of this article is to provide a review of the discussions on this topic, while attempting to evaluate whether the consensus reached allows the achievement of goals set for the resolution mechanism. The article is composed of five parts. The first part introduces the concept of single supervision over the banking sector and explains the importance of having harmonised resolution rules. The second part discusses the process of reaching a consensus towards the establishment of the Single Resolution Mechanism. That part is followed by a description of the final structure agreed for the mechanism back in 2014. The fourth part outlines the review procedure of the established regulations currently under way. The final part of the article summarises the contents and attempts to identify the core issues that still need to be resolved in order to guarantee reliability of the second pillar of the banking union.